Perancangan Sistem Plug and Play pada Otomasi Lampu menggunakan nRF24L01 dan Protokol MQTT melalui Smartphone - Muhammad Kevin Pratama; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The development of the internet of things occurs because of the Wireless Sensor Network. NRF24l01 is one of the communication modules used in the Wireless Sensor Network. The NRF24l01 communication range is suitable for use in homes and building. NRF24l01 can be implemented in daily activities for example turning off and on lamp. Sometimes there are lamp that are not installed in the lamp fitting and it is unknown when going to turn on the lamp. With this research, slave nodes are made as a driving force to turn on or off the lamp and use electric and infrared current sensors to find out whether there are lamp and nodes sink/gateways that connect the slave nodes to the smartphone application. Communication between slave node and sink/gateway node uses NRF24l01. Communication between sink/gateway node and smartphone application uses the concept of internet of things by using the MQTT protocol to manage its communication and cloudMQTT as a broker that stores data temporarily from these communications. This research uses a plug and play method that is applied when it is first turned on, the slave node will send an introduction to the sink/gateway node to get the address and the sink/gateway node will send the available address. The test results prove that the distance between the slave node and the sink/gateway node affects the delay of sending data, then the reference whether there is a lamp or not is the change in electric current and infrared sensors that detect objects.